Temperature effects on asexual reproduction of the scyphozoan Aurelia aurita s.l.: differences between exotic (Baltic and Red seas) and native (Mediterranean Sea) populations. (13th September 2014) - Pascual, Maria; Fuentes, Verónica; Canepa, Antonio; Atienza, Dacha; Gili, Josep‐Maria; Purcell, Jennifer E.
Abstract: Massive occurrences of jellyfish can cause direct impacts on the economy, especially on tourism and commercial fisheries. Translocation of jellyfish species by humans has caused damaging blooms in new habitats. Aurelia aurita s.l . has been introduced in many locations around the world. To test the potential success of Au. aurita s.l . in various habitats, scyphistomae from different climatic locations (Mediterranean, Red and Baltic Seas) were cultured individually for 201 days at three temperatures (14, 21 and 28 °C) with the same salinity, food and light. We tested the null hypotheses that there were no differences in survival or asexual reproduction (budding and strobilation) amongst populations [native (Mediterranean) and exotic (Red and Baltic)]. Survival of the three scyphistoma populations did not differ significantly across temperatures; however, the Red Sea group had lower survival at all temperatures than did the other populations. Most individuals strobilated at 14 °C. Red Sea scyphistomae strobilated more quickly than Baltic and Mediterranean Sea scyphistomae and produced the fewest ephyrae, whereas Baltic Sea scyphistomae produced the most. Our results indicate that Au. aurita from the Baltic or Red Seas introduced into the Northwest Mediterranean Sea would potentially persist and successfully asexually reproduce there. A new invader could even have greater asexual production than the local Au. aurita s.l . Establishment of the invaders could increase genetic variation of subsequent generations and increase their adaptability to environmental changes. Our results suggest that introduction of exotic Au. aurita s.l . populations could increase jellyfish blooms in the Mediterranean Sea.